Food and feeding habits of Salmostoma untrahi from Bhadra Reservoir, Karnataka - Kiran, B R; Puttaiah, E T (Indian Journal of Fisheries, 2011)
Food and feeding habits of Salmostoma untrahi were studied from Bhadra Reservoir, India, during the period 1998-2000. It is observed that qualitatively, the food of males was similar to that of females but quantitatively there were some differences. The order of preference of the food items were: desmids, bluegreens, chlorococcales, diatoms and zooplankton. Desmids and blue-greens formed the major items of diet almost throughout the year. Desmids were dominant in size groups of 111-115 mm, while, blue-greens, chlorococcales, diatoms, dinoflagellates and zooplankton were dominant in 91-95 mm, 76-80 mm, 96-100 mm, 106-110 mm and 96-100 mm respectively. Feeding intensity in relation to season as well as stages of maturity was studied in both sexes. Active feeding was observed during May and July in males and during January and December in females. Feeding intensity appears to be related to spawning activity, besides food abundance. The species of S. untrahi is a surface to column feeder